Exceptionalist narratives and faceless clip art: Critically analyzing Indigenous history resources found on online curriculum marketplaces. (April 2023) - Rodríguez, Noreen Naseem; Brown, Michael G.; Updegraff, Amy; Vickery, Amanda
Abstract: Although children may come to school with knowledge about Indigenous Peoples, early childhood and elementary educators regularly teach about these topics with outdated, misinformed curricular materials. This article describes a critical content analysis of Indigenous history resources found online by preservice teachers. We analyze preservice teachers' assessment of the resources they discovered using a critical media literacy checklist. The analysis revealed that preservice teachers could pinpoint visual stereotypical depictions but struggled to identify problematic narratives and determine what to teach instead. We argue that for-profit marketplaces cannot be viewed as venues for quality, justice-oriented instructional materials and end with recommendations for teaching Indigenous histories.